The effect of pre-existing HLA sensitization on the renal allograft function according to angionephroscintigraphy results - O. G. Sinyakova; N. E. Kudryashova; E. V. Migunova; N. V. Borovkova; A. V. Pinchuk; N. V. Shmarina (Трансплантология (Москва), 2018)
An important role in assessing the transplanted kidney function recovery and diagnosing posttransplant complications belongs to angionephroscintigraphy allowing a qualitative and quantitative assessment of renal perfusion, filtration, and excretion. The aim of the study was to evaluate and monitor the allograft function after cadaveric kidney transplantation by using angionephroscintigraphy with 99mTc-Pentatech and studying the obtained results in relation to pre-existing HLA sensitization. We analyzed the results of radionuclide tests of 55 patients in the early postoperative period in time from 5 days to 3 months after transplantation. In most patients, the higher was the blood anti-HLA antibody levels in the recipient before the kidney transplantation, the more pronounced decrease in the function was noted in them according to angionephroscintigraphy results. In the treatment of patients with a primary allograft function, the function of the transplanted kidney had gradually improved by the 3–4th week, reaching normal values in a number of parameters. In patients with a delayed allograft function, only partial recovery of function was observed after 3–4 weeks. In that case, when a high level of preexisting anti-HLA antibodies had been noted, an abrupt decline in perfusion typical for an acute rejection crisis, and the filtration impairment were seen, often there was an impaired excretion, indicating a concomitant severe ischemic injury of the kidney or acute tubular necrosis. Thus, angionephroscintigraphy enables to assess the recovery of the graft function thanks to a separate evaluation of the function components, and in combination with the test for preexisting anti-HLA antibodies, helps to make a differential diagnosis of an acute rejection crisis and acute tubular necrosis allowing the choice of an adequate treatment tactics.